The Considerations for the Prescription of Valproate as Treatment in Mayo Mental Health Service - Irene Akashie; Rachael Ayodele; Philippa Renton; Sharon Coen; Catherine Kelly (BJPsych Open)
Aims: To examine current monitoring practices for valproate users within Mayo Mental Health Services and analyse the conditions for which it is prescribed.